Agricultural yield and profit prediction using data analysis techniques - Hassan, Fazal Mahmud; Zakir, Shamma Binta; Binta, Anik Shamma; Hossain, Syed Maruf (2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.